FAKTOR YANG BERHUBUNGAN DENGAN STATUS GIZI PENYANDANG AUTISM SPECTRUM DISORDER (ASD) DI SEKOLAH KHUSUS WILAYAH JABODETABEK TAHUN 2023: Faktor yang Berhubungan dengan Status Gizi Anak dengan Autism Spectrum Disorder (ASD) di Sekolah Khusus Wilayah JABODETABEK Tahun 2023 - Ramadhanty, Citra; Simanungkalit, Sintha Fransiske; Octaria, Yessi Crosita; Maryusman, Taufik (Amerta Nutrition, 2024)
Background: The prevalence of Autism Spectrum Disorder (ASD) in Indonesia was predicted to increase by 500 people annualy form 2010, and there are still many nutrition problems found in this group. Nutritional status in ASD is affected by several factors, including mother's education level, parenting style, knowledge of balanced nutrition and parental income. Objectives: To analyze the relationship between mother's education level, parenting style, knowledge of balanced diet and parental income on the nutritional status of persons with ASD in Special Schools in the JABODETABEK (Jakarta, Bogor, Depok, Tangerang, Bekasi) area. Methods: This study was an observational study with a cross-sectional design. The population in this study were people with ASD in Special Schools in the JABODETABEK area. Sampling was conducted using the Quota Sampling method, conducted in March-May 2023 with a total sample of 114 respondents. The data analysis used was the Spearman rank test. Results: Results showed that children and adolescent with ASD in our study had a good nutritional status (average Z-Score=0.81). The bivariate test shows that there was a fairly strong relationship between parenting style (p-value=0.007; r=0.250) and the nutritional status of children and adolescent with ASD. However, there was no relationship between the mother's education level (p-value=0.949), knowledge of balanced diet (p-value=0.728), and parental income (p-value=0.976) with the nutritional status of people with ASD. Conclusions: Parenting style shows a significant positive correlation with the nutritional status of people with ASD in Special Schools in the JABODETABEK area.